A Preliminary Study of the Contractual Regulations of the Tengchow College - GUO , Jianfu (Journal of Research for Christianity in China (JRCC), 2025)
As a Christian university, the Tengchow College established an advanced educational management system, nurturing a cohort of progressive intellectuals in modern China. This article seeks to explore the cultivation of the academy's legal spirit by analyzing the contractual ethos embodied by figures like Calvin Wilson Mateer and the institutional regulations of the Tengchow College.
Keywords: Calvin Wilson Mateer Tengchow College Contract System Student Clubs